Penerapan Fuzzy Multidimensional Association Rule untuk Analisis Pola Perilaku Konsumen - Rouza, Erni; Refni, Nurmia; Antoni, Rivi; Supriyanto, Asep (Journal of Information System and Technology (JOINT), 2024)
Rumah Oleh-oleh Qiran, the largest souvenir center in Rokan Hulu, Riau Province, is experiencing issues with manual inventory and sales tracking, a lack of sales data analysis, and inadequate product arrangement. This study used the Fuzzy Multidimensional Association Rule Algorithm to analyze sales data and generate product association patterns. The main goal is to increase the inventory and sales management efficiency while also optimizing product arrangement based on purchase patterns detected through transaction analysis results. The data used consisted of 140 sales transactions from during June, 2023, with a minimum support 30% and a minimum confidence 25%. The analysis of data results the best-selling products are "Kue Bangkit" (33.58%) and "Gula Aren Rambah Kotak" (27.01%). "kue bangkit" and "gula aren rambah kotak" are the popular product combinations, with a support of 19.71% and a confidence of 72.97%. The application passed the User Acceptance Test (UAT) with a 75% score, indicating that it is applicable to use.